The EFFECT OF DEMONSTRATION VIDEO ON IMPROVING KNOWLEDGE OF BASIC LIFE SUPPORT (BLS) AMONG HOUSEWIVES - AZRY RIZKY WAHYUDI; Niken Anggraini Sri Saputri; Heri puspito (Journal of Indonesian Anesthesiology Nursing, 2026)
Background: Cardiovascular diseases, including sudden cardiac arrest, remain one of the leading causes of mortality worldwide. Unfortunately, approximately 70–80% of cardiac arrest incidents occur outside hospital settings, and only a small proportion of victims receive appropriate immediate assistance. Housewives represent a key community group that may be among the first responders capable of providing Basic Life Support (BLS) during emergency situations. Objective: This study aimed to assess the knowledge of housewives regarding Basic Life Support (BLS) at TK Negeri (State Kindergarten) 01 and to determine the effect of demonstration video education on improving their BLS knowledge. Methods: This study employed a pre-experimental design using a one-group pretest–posttest approach. A total of 59 housewives were recruited through purposive sampling. Data were collected using a 10-item BLS knowledge questionnaire. The intervention consisted of educational demonstration videos on Basic Life Support. Data were analyzed using the Wilcoxon signed-rank test. Results: The findings demonstrated an improvement in participants’ knowledge following the intervention, with the majority of respondents shifting from the “low” knowledge category to the “high” category. The Wilcoxon test revealed a statistically significant difference between pretest and posttest scores (p = 0.000; p < 0.05), indicating that the intervention significantly improved participants’ knowledge of Basic Life Support. Conclusion: Demonstration video education is effective in improving housewives’ knowledge of Basic Life Support (BLS) in responding to medical emergency situations. Recommendation: It is recommended that BLS education be provided regularly to housewives to enhance their preparedness and ability to respond effectively to emergency situations. Keywords: Basic Life Support, Demonstration Video, Preparedness References: 70 references (2021–2025)